2014
DOI: 10.1002/jbm.a.35330
|View full text |Cite
|
Sign up to set email alerts
|

Metallic wear debris may regulate CXCR4 expressionin vitroandin vivo

Abstract: CXCR4, the chemokine receptor for CXCL12, also known as SDF-1 (stromal cell derived factor-1), has been shown to play a pivotal role in bone metastasis, inflammatory, and autoimmune conditions but has not been investigated in periprosthetic osteolysis. We co-cultured osteoblast-like cells with increasing concentrations of metallic (Co-35Ni-20Cr-10Mo and Co-28Cr-6Mo) and Co-ions simulating wear debris. Real-time polymerase chain reaction (RT-PCR) and Western blotting were used to quantify gene and protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…However, in terms of chemotaxis of OCPs, thus far, only SDF-1 was reported to plays a chemotactic role for OCPs for their migration to a bone tissue (22, 4446) . The engagement of CXCR4 for chemotaxis of OCPs in the development of various peripheral osteolytic lesions has only recently been reported (24, 47) . Nonetheless, the importance of MIF in the migration of CXCR4 + OCPs was never addressed in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in terms of chemotaxis of OCPs, thus far, only SDF-1 was reported to plays a chemotactic role for OCPs for their migration to a bone tissue (22, 4446) . The engagement of CXCR4 for chemotaxis of OCPs in the development of various peripheral osteolytic lesions has only recently been reported (24, 47) . Nonetheless, the importance of MIF in the migration of CXCR4 + OCPs was never addressed in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the relevance of chemotactic receptor CXCR4 in the migration of OCPs under physiological conditions has been reported (9) . Moreover, a recent study showed that CXCR4 expression is upregulated on the surface of leukocytes in response to the challenge with metallic wear debris in both in vitro and in vivo contexts (24) . Nevertheless, to the best of our knowledge, no study has addressed the involvement of the MIF/CXCR4 axis in the induction of OCP chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Abrasive wear particle suspensions of two metal alloys containing chromium/cobalt/molybdenum with or without nickel elicited an increase in CXCR4 mRNA and protein in human osteoblastic cell lines [84]. The wear particle suspensions increased TNFa, an effect that was attenuated by the AMD3100.…”
Section: Roles Of CXC and Cc Chemokines In Implant Osseointegration Amentioning
confidence: 98%
“…Mouse macrophage cell lines (RAW264.7) were the most used [4,6,27,28,29,30,31,32,33,34,35,36,37], followed by OB precursors derived from mouse calvaria (MC3T3-E1) [27,28,38,39,40,41] and human (Saos-2 and MG-63) [1,42,43] or rat (ROS 17/2.8) [44] osteosarcoma and monocitic (THP-1) [20,45,46] cell lines. In addition, other studies also used primary cells: mouse [28,47] or human [42,48] OBs, mouse or rat bone-marrow-derived macrophages (BMM) [28,49,50,51], human MSCs [39,52], mouse [47] or human [53] FBs and mouse peritoneal macrophages [54].…”
Section: Gene Expression In Osteolysismentioning
confidence: 99%
“…This procedure leads to an improvement of pain and joint functionality, and the number of THR and TKR amounts to 1.5 million every year [1,2,3]. Given the increase of the life span and of implants in young active patients, this number is expected to increase even further in the coming years (nearly 5% per year) [3,4] and, in 2030, THR will have increased by 154% worldwide [5].…”
Section: Introductionmentioning
confidence: 99%